Atmospheric and oceanic signals for the interannual variability of warm-season flood-inducing rainfall frequency over the middle and lower reaches of the Yangtze River basin - Wang, Jing; Ma, Yue; Liang, Ping; Cao, Xinpei; Zhang, Zhiqi; He, Jinhai (Climate dynamics, 2024)
In China, the middle and lower reaches of the Yangtze River basin (MLRYRB) is a core region suffering frequent devastating floods triggered by heavy precipitation during warm seasons, exerting serious impacts on society. However, the physical mechanisms responsible for the increasing flood-inducing rainfall (FIR) frequency over MLRYRB during warm seasons remain unclear. Based on objective definition procedures, the present study investigates the salient atmospheric and oceanic signals tied to the interannual fluctuations of warm-season FIR frequency over MLRYRB. The results show that the suppressed convection from the remote western Pacific to the east of the Philippines could serve as a salient synchronous atmospheric signal for the increased FIR frequency. Moreover, the sea surface temperature (SST) warming over the tropical Indian Ocean (TIO) and the preceding wintertime El Niño-related SST anomaly pattern are deemed as salient contemporaneous and precursory oceanic signals linking the enhancement of the warm-season FIR frequency over MLRYRB on the interannual timescale, respectively. Further observational evidence and tropical Pacific pacemaker experiment results based on the Community Earth System Model Version 2 (CESM2) suggest that the mature El Niño in the prior winter can exert a delayed impact on the enhanced FIR frequency over MLRYRB during the subsequent warm season by exerting vital contributions to the FIR-favorable systems (i.e., southwestward-shifted western North Pacific anomalous anticyclone and the southward-displaced East Asian subtropical westerly jet). The basin-wide positive TIO SST anomalies act as El Niño’s capacitor to relay its impact. These signals have important implications for seasonal prediction of FIR frequency over MLRYRB, and it is essential to place a high requirement on consideration of the better-known El Niño’s cross-season atmospheric teleconnection.